2007
DOI: 10.1021/jp0702393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Normal and Inverted Gold−Silver Core−Shell Architectures in β-Cyclodextrin and Their Applications in SERS

Abstract: Beta-cyclodextrin (β-CD) in alkaline solution has been observed to produce mono-and bimetallic nanoparticles of silver and gold and to provide in-house stability to both types of particles. Thus, the weak reducing capability of the β-CD molecule (oxidation occurs at +1.33 V vs Ag/AgCl) and its unique kinetic control over the evolution of both normal and inverted core-shell bimetallic architectures have been established. The structure and composition of the bimetallic particles were characterized by UV-visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
248
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(267 citation statements)
references
References 61 publications
18
248
1
Order By: Relevance
“…This was attributed to the slow depletion of the Au-rich shell layer with each ion-bombardment, which was supported by evidence from the thin-beam EDX measurements of the Ag-Au core-shell particle nature. Both the bimetallic Ag-Au particles, in addition to the Au-Ag core-shell structures, were formed by a seed-mediated synthesis capped with beta-cyclodextrin surfactant in alkaline solutions by Pande et al [86] The bimetallic colloids were investigated by XPS, which revealed metallic states for the gold and silver within the core/shell in each case. No surface oxidation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…This was attributed to the slow depletion of the Au-rich shell layer with each ion-bombardment, which was supported by evidence from the thin-beam EDX measurements of the Ag-Au core-shell particle nature. Both the bimetallic Ag-Au particles, in addition to the Au-Ag core-shell structures, were formed by a seed-mediated synthesis capped with beta-cyclodextrin surfactant in alkaline solutions by Pande et al [86] The bimetallic colloids were investigated by XPS, which revealed metallic states for the gold and silver within the core/shell in each case. No surface oxidation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] This phenomenon has been applied to electrocatalytic 14,15,17 and spectroscopic applications. 16 Early examples demonstrating the importance of Pt-shell nanoparticles as active electrocatalysts for the ORR were reported by Adzic and coworkers. 14,15,18 The relationship between bimetallic nanoparticle structure and catalytic activity has been correlated to DFT calculations by a number of groups.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Synthesis of core/shell bimetallic nanowires was utilized to increase the SERS activity, similar to that utilized for spherical nanoparticles. [20,36] Although single nanowire-SERS activity can in fact be achieved with a proper selection of growth modes and polarization conditions, the overall SERS activity is generally compromised due to reduced interaction with the laser beam because of the absorption shift associated with longitudinal resonances far into the infrared region. [28,37] The close match of the lattice spacings for silver and gold and their tendency towards mutual displacement are favorable for alloyed nanoparticles, but not desirable for core/shell nanoparticles, which are composed of separated layers of distinctive elements.…”
mentioning
confidence: 99%